Evaluation Of E-Ifrad Courseware As A Teaching Aid Material (Tam) In Qira’at Studies - Norazman Alias; Zulkifly Mohd Zaki; Zainora Daud; Anuar Hasin; Abdul Mun’im Hilmi (UMT Press, 2026)
Indexed by ERA / MYCITE